2008
DOI: 10.1021/ar800097s
|View full text |Cite
|
Sign up to set email alerts
|

A Decade Journey in the Chemistry of Sandwich-Type Tetrapyrrolato−Rare Earth Complexes

Abstract: Phthalocyanines and porphyrins are versatile functional pigments with a wide range of applications. These macrocyclic compounds contain four isoindole or pyrrole nitrogen atoms, which can complex with a range of metal ions. Large rare earth metal ions can bring together these tetrapyrrole derivatives to form sandwich-type double- and triple-decker complexes. Depending on the metal centers and the nature of the macrocyclic ligands, these compounds exhibit tunable spectroscopic, electronic, and redox properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
177
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 342 publications
(180 citation statements)
references
References 54 publications
1
177
0
2
Order By: Relevance
“…DRAS of monolayers are shown in Figure 5 with the UV−vis spectrum of the complex solubilized in chloroform at a concentration of 1.6 × 10 −5 M. This last one ( Figure 5, curve 1) is characterized by the presence of two intense bands at 650 and 700 nm (Q bands) and a broad band centered at 500 nm, that is typical for the bisphthalocyanine compounds. 18,25,26,34,47,48 The band at 500 nm indicates the presence of an unpaired electron in the double decker crown phthalocyaninate. The ratio of intensities of bands at 650 and 700 nm is indicative of the valent state of the cerium atom: in the case of Ce 4+ short wavelength part of the Q band is prevalent, and in the case of Ce 3+ , this part 4 Pc] 2 LBF on mica substrate obtained in contact mode after a scratching experiment.…”
Section: Resultsmentioning
confidence: 99%
“…DRAS of monolayers are shown in Figure 5 with the UV−vis spectrum of the complex solubilized in chloroform at a concentration of 1.6 × 10 −5 M. This last one ( Figure 5, curve 1) is characterized by the presence of two intense bands at 650 and 700 nm (Q bands) and a broad band centered at 500 nm, that is typical for the bisphthalocyanine compounds. 18,25,26,34,47,48 The band at 500 nm indicates the presence of an unpaired electron in the double decker crown phthalocyaninate. The ratio of intensities of bands at 650 and 700 nm is indicative of the valent state of the cerium atom: in the case of Ce 4+ short wavelength part of the Q band is prevalent, and in the case of Ce 3+ , this part 4 Pc] 2 LBF on mica substrate obtained in contact mode after a scratching experiment.…”
Section: Resultsmentioning
confidence: 99%
“…37 There are 4n+2 π electrons in the middle of phthalocyanines. It was revealed that the π electrons are strongly delocalized around the chromophore, which renders high thermal and chemical stability that can endure intense electromagnetic radiation.…”
Section: Phthalocyanines and Porphyrin Derivativesmentioning
confidence: 99%
“…[14] The typical approach consists in stepwise construction of the target molecule starting from the formation of lanthanide mono-porphyrinate or phthalocyaninate, with subsequent introduction of the following ligand or its precursor. [11,[15][16][17] Another case is the interaction between in situ generated lanthanide mono-porphyrinate and a pre-synthesized double-decker complexes. [17][18][19] Altogether these approaches allow preparation of various heteroleptic lanthanide complexes containing equal or different metal centers for electrochemical or magnetic application.…”
Section: Introductionmentioning
confidence: 99%